NbC-TiN co-precipitation behavior and mechanical properties of X90 pipeline steels by critical-temperature rolling process. (August 2018) - Zhang, J.M.; Huo, C.Y.; Ma, Q.R.; Feng, Y.R.
Abstract: The X90 pipeline steels containing Nb and Ti elements have been produced by special critical-tempering rolling process (CTRP) and conventional thermomechanical controlled process (TMCP) respectively. Microstructure was investigated with field emission scanning electron microscopy (FESEM) and field emission transmission electron microscopy (FETEM), and Mechanical properties were measured by tensile test and charpy impact test. Results show that almost two times impact toughness with similar strength level for CTRP steel was obtained compared with TMCP steel. The averaged thickness of pancaked austenite grain is 7.8 μm for CTRP steel, which is less than a half of TMCP steel whose averaged thickness is 18 μm. In addition, high density NbC-TiN co-precipitates in CTRP steel have been found. However, a small quantity of single NbC and TiN precipitates are observed in TMCP steel. The reason is that CTRP process induced co-precipitation of NbC-TiN particles that promoted epitaxial precipitation of NbC on pre-existing TiN precipitate. High intensity TiN-NbC co-precipitates in CTRP steel promoted adequate Zener drag to retard pancaked austenite growth and improved mechanical properties. Graphical abstract: A new critical-temperature roll process (CTRP) was developed to manufacturing X90 high strength pipeline steel. The CTRP process induced high intensity NbC-TiN co-precipitation at rough rolling stage. As a result of NbC-TiN co-precipitation, ultrafine microstructure and outstanding mechanical properties of CTRP X90 steel were obtained compared with conventional TMCP X90 steel. Averaged size of pancaked austenite for CTRP steel was only 7.8 μm and less than a half of TMCP steel. High intensity co-precipitates are observed in CTRP steel, these co-precipitates have irregular shape and averaged size is about 100 nm. Highlights: A new critical-tempering rolling process for X90 pipeline steel was developed. Ultrafine microstructure of CTRP X90 steel was obtained as a result of CTRP process induced NbC-TiN co-precipitation. Mechanical properties of CTRP X90 steel were more outstanding than conventional TMCP X90 steel.